The Use of PFSense and Suricata as a Network Security Attack Detection and Prevention Tool on Web servers - Sufardy, Devander Benaryanta; Widiasari, Indrastanti Ratna (INOVTEK Polbeng - Seri Informatika, 2024)
This research explores the effectiveness of PFSense and Suricata integration in detecting and preventing network security attacks on web servers. The experimental method was conducted by testing the performance of these two open-source tools in the face of four types of attacks: Ping of Death, SYN Flood, SQL Injection, and Brute Force Attack on SSH. The tests were conducted in an environment with hardware specifications such as [specify specifications, e.g. CPU, RAM, and device type], and software including [specify operating system and version of PFSense and Suricata]. The results showed that Suricata was able to detect threats with an accuracy rate of 92% and successfully blocked 85% of the attacks. The average response time of the system to detect attacks was 250 ms. The integration between PFSense and Suricata proved effective in identifying attack patterns and preventing further potential damage. With proper configuration, this combination not only keeps the web server network secure, but also provides a quick response to complex cyber threats. This research contributes to the development of more reliable network security solutions by demonstrating how the integration of PFSense and Suricata can be effectively used to protect web servers. The findings provide practical guidance for practitioners and academics in implementing more innovative approaches to enhance network security in the digital era.